Effectiveness of Initial Solution Methods in Terms of Logistics Costs: A Maritime Supply Chain Application Based on Marble Exports - Özkan, Hakan (International Journal of Contemporary Economics and Administrative Sciences, 2025)
This study compares three widely used initial solution methods for transportation problems—the Northwest Corner Method, Least Cost Method, and Vogel’s Approximation Method—within the context of maritime transportation. The research employs a two-stage methodology: first, determining the optimal solution via Linear Programming; second, generating initial solutions using the three methods. The dataset comprises marble exports transported by sea from the Western Mediterranean Region in 2024, provided by the Western Mediterranean Exporters Association. Analysis was conducted using Microsoft Excel and its Solver add-in. Results indicate that Vogel’s Approximation Method yields an initial solution closest to the optimal. Consequently, the methods are ranked as follows for maritime transportation problems: Vogel’s Approximation Method first, Least Cost Method second, and Northwest Corner Method third. These findings offer practical guidance to maritime sector practitioners and decision-makers by aiding in the selection of the most efficient method in terms of time and resource optimization when solving transportation problems.